Management Strategies for Choledochal Cysts in Infants and Children Our Experience at Department of Pediatric Surgery ,L.R.H, Peshawar - Muhammad Younas Khan, Syed Asad Maroof, Fayaz Iqbal, Wardah Saleem, Muhmmand Shoaib, Kifayat (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study aims to understand more about choledochal cysts and how they are managed in children under 12 years old. Setting and Design: A Descriptive Study at Department of Pediatric surgery L.R.H. Hospital Peshawar. Method and Material: The most common kind of malformation of the biliary tree in Pakistan is choledochal cyst malformation (C.C.M.). Congenital choledochal anomalies range from asymptomatic to life-threatening cholangitis or pancreatitis. Surgeons now recommend total cyst ectomy and bilioentenric anastomosis. This five-year research examines. Clinical presentation, blood and laboratory testing, imaging, surgery, and predictive data were evaluated from case records. Twenty-three children with choledochal cysts were treated between January 2019 and December 2021, and their clinical presentation, diagnostic tests, and treatments were recorded. ERCP or a cholangiogram confirmed choledochal cysts after ultrasound diagnosis (P.O.C.). Before surgery, children with cholangitis received antibiotics and percutaneous transhepatic biliary drainage (excision of the cyst and jejunal loop interposition hepaticoduodenostomy) Results: Twenty-three patients were analyzed; eight presented with chronic abdominal pain, five with a history of cholangitis, two with acute cholangitis, four with biliary peritonitis, and one with a history of pancreatitis. Following cyst excision, Roux-en-Y hepaticojejunostomy (RYHJ) was performed in 13 patients, and hepaticoduodenostomy (H.D.) was performed in 4 patients. One example of congenital choledochal malformation type II was treated with cyst excision and drainage because cholangitis and jaundice threatened the patient’s life. The median age was 3, and the gender distribution was about even. Of the patients who sought care, 18 presented with jaundice, 15 with abdominal discomfort, 12 with fever, and 9 with a mass in their stomach. Only four people had all three symptoms of characteristic jaundice, pain, and lump. Overall, the results of both ERCP in 7 patients and P.O.C. in 14 cases were favorable. There were two distinct clinical presentations: I infantile form (less than a year), which included nine infants with jaundice in all, acholic stool in 7, lump abdomen in 4, but only one with classical triad; and (ii) childhood form (more than a year), which included twelve patients with abdominal pain, jaundice, and cholangitis. Twenty patients had a type I cyst, and three had a type Iva cyst. Only two kids said no to surgery, while the rest went through with it. Only three newborns were lost during surgery, but the other 18 did well following their follow-up visits (median 25 months). Six had extrahepatic biliary atresia, two had congenital hepatic fibrosis, and one had congenital biliary cirrhosis. Practical implication: Our study will provide a new data to the health care providers about choledochal cysts and how they are managed in children under 12 years old Conclusions: However, total cyst removal and Roux en Y hepaticojejunostomy (RYHJ) anastomosis is the definitive treatment of Congenital Choledochal Malformation. However, several other temporary therapies are also necessary at various phases of the illness. Their criticality—evolutionary stages may differentiate two types of choledochal cysts from infancy through adulthood. The prognosis is favorable following surgery, but early identification and referral are critical for reducing the risk of complications and mortality. Keywords: Choledochal cyst, ERPC, H.D., RYHJ, and C.C.M. (Endoscopic retrograde cholangiopancreatography)